African cinemas : decolonising the gaze - Barlet, Olivier (London ; New York : Zed Books, 2000)
"Focusing on the attempt to decolonize the imagination, this book is both a personal journey and an introduction to the cinema cultures of Africa. A book about the politics of cultural survival, it is also a major overview of African cinema and television." "The first part traces the development of African cinema - from colonization to Afrocentrism. The second part of the book analyses specific films, particularly through narrative and in terms of their African specificity in the use of silence, orality and humour. Finally, the author explores the social and economic contexts of the African cinema and television industry - including its often vexed relations with the West and the problems of production and distribution African film-makers face."
"Exploring the achievements and challenges of those who seek to affirm African cultural values through film, the book also covers the African television industry and African-American cinema. It includes interviews with film-makers, stills from the films and, ultimately, a plea for seeing and respecting the otherness of the Other. The French National Film Centre's best film book of 1997 and now available in four languages, this is a book which takes us into a process of learning how to look."--BOOK JACKET.
Includes bibliographical references and index.
Translated from French.
Keywords: Motion pictures -- Africa, Sub-Saharan -- History; Cinematography -- Africa; Mass media -- Africa